2018
DOI: 10.1371/journal.pmed.1002653
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the quality of tuberculosis care in urban India: A cross-sectional, standardized patient study in two cities

Abstract: BackgroundIndia has the highest burden of tuberculosis (TB). Although most patients with TB in India seek care from the private sector, there is limited evidence on quality of TB care or its correlates. Following our validation study on the standardized patient (SP) method for TB, we utilized SPs to examine quality of adult TB care among health providers with different qualifications in 2 Indian cities.Methods and findingsDuring 2014–2017, pilot programs engaged the private health sector to improve TB manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 26 publications
4
115
0
Order By: Relevance
“…However, disaggregating the data about TB cases by place of residence offset the high CNR in urban and low CNR in adjacent communities, which could give the real picture of TB case notification in the areas. Like other studies in urban populations [19][20][21], studies from Ethiopia show that the urban population, representing only 8% of the country's population, contributed 11% of the total TB cases notified [22]. This phenomenon could be due to patients coming from neighboring catchment areas for access to better diagnostics and availability of technical expertise, thereby increasing urban poverty, overcrowding, urban migration, HIV infection, and disease transmission [9].…”
Section: Discussionmentioning
confidence: 92%
“…However, disaggregating the data about TB cases by place of residence offset the high CNR in urban and low CNR in adjacent communities, which could give the real picture of TB case notification in the areas. Like other studies in urban populations [19][20][21], studies from Ethiopia show that the urban population, representing only 8% of the country's population, contributed 11% of the total TB cases notified [22]. This phenomenon could be due to patients coming from neighboring catchment areas for access to better diagnostics and availability of technical expertise, thereby increasing urban poverty, overcrowding, urban migration, HIV infection, and disease transmission [9].…”
Section: Discussionmentioning
confidence: 92%
“…The implicit and critical assumption behind this strategy is that qualified HCPs will prescribe or dispense antibiotics responsibly and that directing patients towards qualified HCPs, and away from unqualified HCPs, will reduce inappropriate use of antimicrobials [15]. However, when HCP professionalism is lacking, boundaries between qualified HCPs and unqualified providers can be blurred [17,18]; for example, qualified providers may routinely fail to follow treatment guidelines [19] or regulations around prescribing [20], and informal providers may demonstrate more empathy towards patients than qualified HCPs [17,21]. We therefore hypothesise that weaknesses in the professionalism of HCPs-including doctors, pharmacists, and nurses-will have an impact on inappropriate use of antibiotics, and we investigate this in two LMIC, Pakistan and Cambodia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, referral links to the National Tuberculosis Programme are weak, with data from standardised patient studies in these three countries showing that only 28% to 45% of patients were correctly managed by primary care providers. 34,35,46 Simply put, the global capacity to diagnose, link to care, treat, and cure patients with tuberculosis is woefully inadequate for the massive burden of disease that exists. The public health implications, as well as the poor clinical and financial implications for patients, 41 are self-evident.…”
Section: Insufficient Investment and Political Willmentioning
confidence: 99%
“…Unfortunately, cascade of care analyses shows large gaps in the quality of care for both adults and children, and for both drug-susceptible and drug-resistant tuberculosis in many high-burden countries. [36][37][38]112,133 Standardised patient studies in India, Kenya, South Africa, and China [33][34][35]46 have shown that the quality of care for tuberculosis is poor. In a study in China, for example, health-care providers did not correctly manage patients presenting with archetypal symptoms or results suggesting active tuberculosis 59% of the time.…”
Section: Improving Quality Management To Ensure High-quality Service mentioning
confidence: 99%